Experimental investigation on the influence of high temperature on viscosity, thermal conductivity and absorbance of ammonia–water nanofluids. (October 2017) - Jiang, Weixue; Du, Kai; Li, Yanjun; Yang, Liu
Highlights: The influence of high temperature on viscosity, thermal conductivity and absorbance of nanofluids is investigated. The effects of surfactant may be greatly reduced or even destroyed after heating at high temperature. Properties of nanofluids have tremendously been altered or even destroyed when hysteresis phenomenon occurs. Prepared γ-TiO2 ammonia–water nanofluid presents the best potential for application in AARS compared to other nanofluids. Abstract: To select the optimal ammonia–water nanofluids and apply to ammonia–water absorption refrigeration systems (AARS), this paper investigated the influence of heating on viscosity, thermal conductivity and absorbance of binary nanofluids. The hysteresis phenomenon was observed after heating at high temperature which is rarely reported in the literature. Experimental results show that most of nanofluids' thermal conductivity increased by about 3–12% after heating. However, their viscosities increased by as much as 15% to 25% except the γ-TiO2 ammonia–water nanofluid, which was reduced by 2% to 7%. This study also shows that the trend of viscosity is consistent with the absorbance. Due to fact that the thermal conductivity of γ-TiO2 /NH3 –H2 O mixture increased after heating, while the viscosity decreased, even if the concentration of the base liquid is 12.5% or 25%, therefore it is the optimal choice for practical research in AARS at present.